The Future of Learning: Pedagogical Paradigms in the Age of Artificial Intelligence through the Advent of ChatGPT as an Innovative Digital Tool in the Era of Technology - Rasha Abdulraheem (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2025)
The rapid emergence of Generative Artificial Intelligence (AI) tools, particularly ChatGPT, has reshaped contemporary education by addressing the growing demands of the 21st century, where traditional teaching methodologies are no longer sufficient to meet learners’ evolving needs. This study aims to examine the pedagogical and ethical implications of integrating ChatGPT into English as a Second Language (ESL) instruction, situating the analysis within UNESCO’s Sustainable Development Goal 4 on quality education. Employing a qualitative, literature-based design, this paper synthesizes recent empirical and conceptual research published between 2018 and 2025 to evaluate both the opportunities and limitations of AI-enhanced pedagogy. The findings reveal that ChatGPT supports language acquisition by enhancing interaction, scaffolding productive and receptive skills, and fostering learner autonomy and creativity. However, issues related to ethics, digital equity, and responsible use remain significant challenges. The study concludes that successful integration of ChatGPT requires evidence-based pedagogical frameworks and unified AI policies to ensure ethical, inclusive, and sustainable educational transformation.